Thermal Performance of Low-Cost House with Retrofit Solutions - T. Y. E., John; W. A. W. Z., Abidin; T., Masri; A., Baharun (ENCON 2013, 2013)
Cooling systems play an important role to maintain the desired comfort level of indoor environment. Passive cooling system is one of the cooling techniques which are widely used in housing and building development. It includes the application of natural processes and passive technologies to remove heat without the usage of conventional cooling system. Passive technologies involve different building envelope designs in reducing the heat absorption and heat conduction of the buildings. For country like Malaysia, cooling is always an issue since its climate is hot and humid. The condition of low-cost houses is a concern as the constructions of these buildings mostly do not consider the thermal comfort within the house. This paper is aimed to present the thermal performance of a selected low cost house in Samariang, Kuching. The performances of the low cost house are evaluated by the experimental data collected and also the simulated results from a software called EnergyPlus. Retrofit solutions which involve passive cooling techniques are done in simulation method to improve the comfortable level within the house.